2003
DOI: 10.1073/pnas.0831229100
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of developmental restrictions in neural crest lineages: Transition from Schwann cells to glial-melanocytic precursors in vitro

Abstract: In vertebrate embryos, diversification of the lineages arising from the neural crest (NC) is controlled to a large extent by environmental factors. In previous work, we showed that endothelin 3 (ET3) peptide favors the development of glial and melanocytic NC precursors in vitro. This factor is also capable of inducing proliferation of cultured epidermal pigment cells and their conversion to glia. ET3 therefore strongly promotes the emergence of melanocytic and glial phenotypes from precursors and acts on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 37 publications
4
101
0
Order By: Relevance
“…Such dependency is consistent with our findings (26) that GM precursors of trunk origin are a privileged target for the survival-and proliferation-promoting effects of ET3 in vitro. The strong potential of ET3 to trigger expansion of GM stem cells may also underlie the capacity of differentiated glial cells and melanocytes to reverse their phenotypic program and transdifferentiate reciprocally in vitro (36,37,53). GM cells isolated from the cephalic NC showed a delayed response to ET3 because they were unaffected by treatment during the first cloning.…”
Section: Discussionmentioning
confidence: 99%
“…Such dependency is consistent with our findings (26) that GM precursors of trunk origin are a privileged target for the survival-and proliferation-promoting effects of ET3 in vitro. The strong potential of ET3 to trigger expansion of GM stem cells may also underlie the capacity of differentiated glial cells and melanocytes to reverse their phenotypic program and transdifferentiate reciprocally in vitro (36,37,53). GM cells isolated from the cephalic NC showed a delayed response to ET3 because they were unaffected by treatment during the first cloning.…”
Section: Discussionmentioning
confidence: 99%
“…The term "reprogramming" was used for the first time, as the conversion of glial cells into melanocytes succeeded [4]. In addition, multipotent rat neural crest stem cells can be derived from embryonic SNs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that Schwann cells are highly plastic cells that are able to differentiate into melanocytes and myofibroblasts, undergo cellular reprogramming, dedifferentiate, and re-enter the cell cycle [4,5]. A hallmark of reprogramming of an adult cell to a stem cell is the alteration of its pattern in gene expression [6].…”
mentioning
confidence: 99%
“…In this respect it is of interest that the T cell clones originally isolated from a patient with leprosy that were used to demonstrate reactivity towards MHC class II expressing melanocytes were reactive with mycobacterial stress protein hsp65 [31]. This is noteworthy, particularly since Schwann cells harbor the causative M. leprae organism in leprosy, whereas Schwann cells are developmentally very closely related to melanocytes [35]. This similarity may ultimately contribute to cross reactivity or epitope spreading from Schwann cell antigens to melanocytes, explaining the similarity among lesions observed in tuberculoid leprosy and autoimmune vitiligo.…”
Section: Involvement Of T Cells In Depigmentationmentioning
confidence: 99%